Flotation of sulfur polymetallic cooper-lead-zinc minerals - Azañero Ortiz, Angel (2010)
Polymetallic sulfide ores are found in abundance in nature and especially in our country, hence the great importance of studying their behavior in the differential flotation. There are ores that are very amenable to flotation and there are also other complex minerals that have a very complicated flotation because of different factors, the most difficult ones are those with natural activation of sphalerite and iron sulphides due to soluble salts that the mineral can have as a result of the presence of metal ions from different metals, mainly copper. The copper, lead and zinc ore that was studied did not show difficulties during the selective flotation; the quality and the separation efficiency of concentrates can be improved with more time and more stages of flotation cleaning. We defined the theoretical concepts of the selective flotation and made the mineralogical and chemical study of the sample. The bulk flotation tests and the separation reported good results. We can mention that the gold content in the lead-copper concentrate provides an economic value of $ 380 dollars for TMC.